In situ carcinoma developed over oral lichen planus: a case report with analysis of BUB3, p16, p53, Ki67 and SOX4 expression - Eduardo Augusto ROSA; Erica Negrini LIA; Sergio Bruzadelli MACEDO; Rivadavio Fernandes Batista de AMORIM (University of São Paulo, 2015)
AbstractOral lichen planus (OLP) represents a common mucocutaneous disease. Various authors have suggested that OLP has malignant potential; however, the mechanisms involved in malignant transformation have not yet been elucidated. A 79-year-old man presented a white lesion for five months in the buccal mucosa diagnosed as OLP. After two months using 0.05% clobetasol ointment for treatment, the lesion became ulcerated. A new biopsy of the same lesion was performed, and histological analysis showed an in situ oral carcinoma (ISOC). An immunohistochemistry panel was performed, and p16 expression was negative in OLP, however, it showed weak cytoplasmic staining in ISOC. There was strong nuclear BUB3 staining in both OLP and ISOC areas. p53 showed less intense nuclear staining in both regions. Ki67 was negative in OLP area, but showed nuclear staining in the ISOC. SOX4 was negative in both studied areas. BUB3 expression, first reported in this case, and the p16 expression may suggest some influence of these genes on pathogenesis or malignant potential of OLP.